The Influence of Kampus Mengajar Literacy Activities on Student Learning Outcomes: A Literature Review - Najamudin Marif; Dwi Muliati; Siti Nuraliyah (Jurnal Pedagogi dan Inovasi Pendidikan, 2026)
Low interest in reading and student learning outcomes in Indonesia are a serious challenge in the field of education. The Kampus Mengajar Program appears as one of the strategic solutions to improve literacy and the quality of learning in schools. This article aims to analyze the influence of literacy activities initiated through the Kampus Mengajar program on student learning outcomes through a literature study approach. The research method used is qualitative with the type of literature review, which examines various relevant reference sources published from 2020 to 2026. The results of the study indicate that the integration of structured literacy activities, such as reading for 15 minutes before learning, significantly contributes to improving students' cognitive, affective, and psychomotor abilities. Literacy is not just the ability to read and write, but a foundation for critical thinking that is positively correlated with academic achievement.